The unique histidine in OSCP subunit of F‐ATP synthase mediates inhibition of the permeability transition pore by acidic pH - Antoniel, Manuela (EMBO Rep, 2017)
The permeability transition pore (PTP) is a Ca(2+)‐dependent mitochondrial channel whose opening causes a permeability increase in the inner membrane to ions and solutes. The most potent inhibitors are matrix protons, with channel block at pH 6.5. Inhibition is reversible, mediated by histidyl residue(s), and prevented by their carbethoxylation by diethylpyrocarbonate (DPC), but their assignment is unsolved. We show that PTP inhibition by H(+) is mediated by the highly conserved histidyl residue (H112 in the human mature protein) of oligomycin sensitivity conferral protein (OSCP) subunit of mitochondrial F(1)F(O) (F)‐ATP synthase, which we also show to undergo carbethoxylation after reaction of mitochondria with DPC. Mitochondrial PTP‐dependent swelling cannot be inhibited by acidic pH in H112Q and H112Y OSCP mutants, and the corresponding megachannels (the electrophysiological counterpart of the PTP) are insensitive to inhibition by acidic pH in patch‐clamp recordings of mitoplasts. Cells harboring the H112Q and H112Y mutations are sensitized to anoxic cell death at acidic pH. These results demonstrate that PTP channel formation and its inhibition by H(+) are mediated by the F‐ATP synthase.